Naukowy hedonizm jako podstawa krytycznej oceny przemian społecznych – ekonomia szczęścia Richarda Layarda, Marka Anielskiego i Richarda Easterlina - Więckowski, Paweł (Annales. Etyka w Życiu Gospodarczym, 2011)
Since about 1970 there is a growing scientific interest in the concept of happiness (or its measurable equivalent – subjective well-beingSWB). It is assumed that if augmenting happiness is assumed as the aim of social development, it can be assessed if real progress is beingmade. It should replace traditional concept of GDP. Researchers like Richard Layard, Mark Anielski and Richard Easterlin use the concept ofhappiness to mount a critique of contemporary free-market capitalism. They suggest that instead of consumption and competition,governments should promote happiness, tightening interpersonal relationship, building social trust, timing strive for prestige. However otherresearchers (Ruut Veenhoven, Betsey Sevenson and Justin Wolfers among others) defend economical growth as a foundation of every socialdevelopment. The discussion has a philosophical paradox in it – those how attack capitalism from a humanistic angle use a hedonistic andselfish concept of subjective happiness while those who defend capitalism appeal to values that goes beyond it.